BISNIS WARALABA DI INDONESIA DALAM PERSPEKTIF HUKUM BISNIS SYARIAH - SYAHRANI, SYAHRANI (Islamic Economics and Business Faculty of UIN Antasari, 2012)
Franchise is a relatively new phenomenon in Indonesias business world, although ithas been common in developed worlds like the United States and European countries. This busi-ness runs according to procedures made by the franchisor. The latter will assist the franchisee, and inreturn, he or she will pay the initial fee and royalty. This business is not contrary to Shariaprecepts, as long as the object of a franchise contract is not something forbidden by Islamic law.Franchise contract accords with terms and conditions of a proper contract in Sharia, avoids ambi-guity, and follows the principles of Ash-Shidq (honesty and trustworthiness) and AI-Kitabah (writ-ten).